Active planar waveguides based on sol-gel Er3+-doped SiO2-ZrO2 for photonic applications: Morphological, structural and optical properties - Goncalves, R. R.; Guimaraes, J. J.; Ferrari, J. L.; Maia, L. J. Q. [UNESP]; Ribeiro, Sidney José Lima [UNESP] (Elsevier B.V., 2008)
Er3+-doped glass-ceramic SiO2-ZrO2 Optical Planar waveguides were prepared by the sol-gel route using different SiO2:ZrO2 molar ratios (90:10, 85:15, 80:20 and 75:25). Multilayered films were deposited onto Si(100) substrates by the dip-coating technique. Structural characterization was performed using vibrational spectroscopy and X-ray diffraction. Some optical properties, densification and surface morphology of these films were investigated as a function of the SiO2:ZrO2 ratio. annealing temperature and time. Optical properties such as refractive index, number of propagating modes and attenuation coefficient were measured at 632.8, 543.5 and 1550 nm, by the prism coupling technique. Uniform surface morphology with roughness less than 0.5 nm. Low losses, less than 0.9 dB/cm at 612.8 nm in the TE0 mode, were measured for the planar waveguides containing up to 25 mol% zirconium oxide. Luminescence of Er3+ in the near infrared was observed for the active nanocomposite. (C) 2008 Elsevier B.V. All rights reserved.
Keywords: Glass-ceramics; Planar waveguides; Atomic force and scanning tunneling microscopy; TEM/STEM; Nanocrystals; FTIR measurements; Silica; Silicates; Sol-gels (xerogels); X-ray diffraction